Karakteristik Klinikopatologik Karsinoma Sel Skuamosa Serviks dan Hubungannya dengan Tumor-Associated Neutrophil - Joko M; Susilawati; Alisa, Nanda Safira; Dewi, Citra; Edi Pudjo, Ika Kartika (Majalah Patologi Indonesia, 2022)
BackgroundCervical carcinoma is one of the most common cancers in women, according to data from World Health Organization (WHO).Cervical carcinoma ranks the fourth most deadly type of cancer. Squamous cell carcinoma is the most common type of this cervicalcancer and it is generally caused by Human Papilloma Virus (HPV) types 16 and 18. Tumor-Associated Neutrophil (TAN) are foundin various types of cancer, the density of TAN can determine the prognostic type of tumor or cancer in each individual. This studywas aimed to identify correlation between clinicopathological characteristics of cervical squamous cell carcinoma (SCC) and TAN incervical SCC patients registered at RSUP Dr. Mohammad Hoesin Palembang.MethodsThis type of research is analytic with a cross-sectional method. Data collection in this study used a 37 slides archive which werediagnosed as cervical squamous cell carcinoma in Anatomic Pathology in RSUP Dr. Mohammad Hoesin Palembang for the periodof 2017-2019.ResultsFrom 37 cervical SCC patients, the clinicopathological characteristics of the majority of cervical SCC patients occurred in the agegroup of 51 year-old (51.4%), with histopathological type of non-keratinizing SCC (75,7%) and the most frequent differentiationdegree was moderately differentiated (75,7%). The TAN density was mostly found at low TAN densities (73%). There wassignificant correlation between age and TAN density (p=0.035) and there was no significant correlation between age and TANdensity (p=0.269).ConclusionIt was explained that the higher the degree of differentiation, the lower the density value, however the neutrophils in this studycannot be ascertained whether the neutrophils of anti-tumor (N1) or pro-tumor (N2) characteristic